Gender Dysphoria and Co-Occurring Autism Spectrum Disorders: Review, Case Examples, and Treatment Considerations - Jacobs, Laura A; Rachlin, Katherine; Erickson-Schroth, Laura; Janssen, Aron (LGBT health, 2014)
Transgender and gender nonconforming people who fulfill diagnostic criteria for autism spectrum disorders (ASDs) often present to mental health providers with concerns that are distinct from those without ASDs. Gender Dysphoria (GD) and ASDs have been proposed to share etiologic mechanisms and there is evidence that ASDs may be more common in transgender and gender nonconforming people. We explore the impact of ASD characteristics on individual gender identity, expression, and the process of psychotherapy. The authors present two case studies of high-functioning individuals with ASD and GD diagnoses. The limited ability to articulate an inner experience, deficits in Theory of Mind (ToM), along with the intolerance of ambiguity as a manifestation of the cognitive rigidity characteristic of ASDs, may present special difficulties to gender identity formation and consolidation and create challenges in psychotherapy. The authors suggest that ASDs do not preclude gender transition and that individuals with high-functioning ASDs are capable of making informed decisions regarding their medical care and life choices. The authors also consider possible challenges and suggest techniques for assisting such clients in exploring their gender identities.